Estudo do processo de comunicação integrada de marketing nas mídias digitais em instituições de ensino superior - Breda, Fernanda (2017)
The Internet and the propulsion of new digital media have become multi-faceted tools of Integrated Marketing Communication, contributing to the coordination of the configuration between the communication elements, in order to generate complementary advantages. In this sense, the research addresses the integrated marketing communication in the context of digital social media in Higher Education Institutions, in order to understand how this process occurs in these organizations. To do so, we used the model proposed by Gurau (2008), which emphasizes that messages published in social media should be in accordance with corporate values, strategies and tactics, and target audience. In order to reach the proposed objective, the research was divided into two parts: the first refers to the literature review relevant to the topic and the second part to the empirical research. The empirical research was carried out based on the exploratory method and qualitative approach, through structured interviews with managers of Higher Education Institutions. The research corroborated with findings from the literature and added new perspectives in the process of integrated marketing communication carried out in digital social media by Higher Education Institutions, such as the relevance of internal communication among collaborators and internal audiences of HEIs. The results point out that the CIM process carried out by HEI in social media is in line with corporate values, strategies and tactics and target audience, however, the process is not planned but rather delineated according to the circumstance.